Визначення залежності рівня глюкози крові від рівня глюкози лімфи - Палінський, І.З. (Медична гідрологія та реабілітація, 2008)
Цель исследования - определение зависимости уровня глюкозы в крови от уровня глюкозы в лимфе при отсутствии сахарного диабета. В результате исследования было доведено, что в лимфе здорового человека глюкоза отсутствует, а уровень глюкозы крови зависим от уровня глюкозы в лимфе и не может повышаться, если уровень глюкозы в лимфе не превышает 6 мМ/л. Показатель уровня глюкозы лимфы с достоверностью 99,99% может характеризовать состояние пациента по отношению к заболеванию сахарным диабетом. Это новейший подход к диагностике сахарного диабета с использованием новейших направлений медицинской науки - вегетативной неврологии и лимфологии. Уровень глюкозы лимфы есть очень существенным и вероятным диагностическим показателем для постановки диагноза сахарный диабет и определения склонности пациента к заболеванию сахарным диабетом, так как этот показатель всегда опережает повышение уровня глюкозы в крови. Определение уровня глюкозы лимфы показало высокий процент (77%) склонности людей к заболеванию сахарным диабетом на современном этапе. Diagnostics of saccharine diabetes on the modern stage uses blood and test-sistemy of analyses of blood tests exceptionally (glyukozovannyy haemoglobin, #-peptid...). In any research of blood or testsisteme of not foreseen the amount of selection of insulin, presence or absence of him, is unchecked in blood, nor in one research or test-sisteme not foreseen and unchecked how many insulin is producted by the aits of Langengarsa. The purpose of this labour is determination of level of glucose in a lymph, got from between cellular space of hypodermic cellulose of overhead surface of foot in default of saccharine diabetes and determination of dependence of level of glucose in blood from the level of glucose in a lymph. It was led to as a result of experiment, that level of glucose of blood is dependency upon the level of glucose in a lymph and can not rise, if level of glucose in a lymph no more approximately 6 mmol/l. Index of level of glucose of lymph, with authenticity 99,99% can characterize the state of patient in relation to a disease saccharine diabetes. It is the newest approach to diagnostics of saccharine diabetes with the use of the newest directions of medical science vegetative neurology and limfology. A level of glucose of lymph is a very substantial and credible diagnostic index for determination of diagnosis saccharine diabetes, determination of inclination of patient to the disease saccharine diabetes, because this index is always passed ahead by the increase of level of glucose in blood. The increase of level of glucose of lymph in 99.99% cases specifies on the threat of increase or increase of level of glucose in blood, and on liability to the disease saccharine diabetes and early diagnostics of disease. The level of glucose of lymph of healthy man is equal 0,00 mmol/l. Determination of level of glucose of lymph showed the high percent (77%) of inclination of people to the disease saccharine diabetes on the modern stage.